The formation of the colonial state in India : scribes, paper and taxes, 1760-1860 - Bellenoit, H. J. A. (Routledge studies in South Asian history ;, 2017)
"In the period between the 1770s and 1840s, through the process of colonial state formation, the early colonial state in India was able to harness and extract vast amounts of agrarian wealth in north India. However, little is known of the histories of the Indian scribes and the role they played in shaping the early patterns of British colonial rule. This book offers a new way of investigating the colonial state's origins in north India. It examines how the formation of early agrarian revenue settlements exacerbated an extant late Mughal taxation tradition, and how the success of British power was shaped by this extant paper-oriented revenue culture. It goes on to examine how the service and cultural histories of various Hindu pensmen/scribal communities fit within broader changes in political administration, taxation, patterns of governance and a shared Indo-Islamic administrative culture. The author argues that British power after the late 18th century came as much through bureaucratic mastery and paper and taxes as it did through military force and commercial ruthlessness. The book draws upon private family papers, interviews and Persian sources to demonstrate how the fortunes of scribes changed between empires, and the important role they played at the height of the British Raj by 1900. Providing a detailed account of how agrarian wealth provided the bedrock of colonial state's later patterns of administration, this book is a unique and refreshing contribution to studies of South Asian History, Governance and Imperialism"--Provided by publisher.